The Miracle in Christianity According to David Hume - Muhammad Alif Rahmadi; Zulfikar Zulfikar (Departement of Comparative Study of Religions, 2021)
This article examines the views of David Hume on miracles in Christianity in his book “An Inquiry ‎Concerning Human Understanding”. Using a literature ‎approach and systematic analysis of David Hume's writings, this research generates ‎several ideas. David Hume wrote that any miracle that happens in this world is a ‎violation of the laws of nature. Miracles destroy the natural order ‎and are not in line with the existing law of nature. David Hume opposed the idea of miracles ‎because he was a religious skeptic, against all things metaphysical and non-natural to ‎humans. Thus, David Hume rejected the truth filled with doubts and questions. David ‎Hume's skepticism leads to the theory of deism, that God is a product of human thought ‎and He does not interfere with what He created.